2016
DOI: 10.1038/srep18595
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-induced negative regulation of TLR-5 in grass carp, Ctenopharyngodon idella

Abstract: MicroRNAs (miRNAs) are endogenous small non-coding RNAs that play crucial roles in numerous biological processes. However, the role of miRNAs in antibacterial defence in fish has not been fully determined. Here, we identified that nine miRNAs are differentially expressed in kidney between susceptible and resistant grass carp strains. Analysis of spatial and temporal miRNA expression patterns suggests that cid-miRn-115 and miR-142a-3p are potential regulators of anti-bacterial activity. Overexpressing of cid-mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 47 publications
2
18
0
Order By: Relevance
“…miR-21 also suppressed the excessive immune response and maintained body homeostasis in miiuy croaker by directly targeting TLR28. The activation of TLR5 could modulate the expression of genes involved in innate immune responses ( 71 ). cid-miRn-115 and miR-142a-3p were differentially expressed between susceptible and resistant grass carps infected with Aeromonas hydrophila .…”
Section: The Functional Role Of Mirnas In Fish Immune Regulationmentioning
confidence: 99%
“…miR-21 also suppressed the excessive immune response and maintained body homeostasis in miiuy croaker by directly targeting TLR28. The activation of TLR5 could modulate the expression of genes involved in innate immune responses ( 71 ). cid-miRn-115 and miR-142a-3p were differentially expressed between susceptible and resistant grass carps infected with Aeromonas hydrophila .…”
Section: The Functional Role Of Mirnas In Fish Immune Regulationmentioning
confidence: 99%
“…The let-7 family is known to regulate multiple genes related to the cell cycle and proliferation (Yang et al, 2008 ), and let-7i was shown to influence innate immunity (Chen et al, 2007 ). Recently, Xu et al ( 2016 ) studied these two carp lineages using two kidney miRNA transcriptomes from SGC or RGC infected with the highly pathogenic A. hydrophila and identified nine miRNAs differentially expressed between these groups. Furthermore, the spatial and temporal expression of a novel miRNA (cid-miRn-115) and miR-142a-3p suggests that they are potential regulators of anti-bacterial activity (Xu et al, 2016 ).…”
Section: A Review Of Mirnas In Farmed Fishesmentioning
confidence: 99%
“…Recently, Xu et al ( 2016 ) studied these two carp lineages using two kidney miRNA transcriptomes from SGC or RGC infected with the highly pathogenic A. hydrophila and identified nine miRNAs differentially expressed between these groups. Furthermore, the spatial and temporal expression of a novel miRNA (cid-miRn-115) and miR-142a-3p suggests that they are potential regulators of anti-bacterial activity (Xu et al, 2016 ). Overexpression of these miRNAs resulted in a visible change in the immune effector activity in C. idella kidney cells, and bioinformatics analysis shows that they directly regulate tlr5 expression (Xu et al, 2016 ), which is associated with the innate immune response (Yoon et al, 2012 ).…”
Section: A Review Of Mirnas In Farmed Fishesmentioning
confidence: 99%
“…Taken together, these results revealed that appropriate regulation of miR-146b expression is critically important for fish to resist infection. However, several reported immune-related miRNAs were not differentially expressed in the three libraries, including let-7 family, miR-155 and miR-192 [58,59,60], probably due to species- or tissue-specific miRNA expression [7,10]. …”
Section: Discussionmentioning
confidence: 99%